Pengembangan Sistem Informasi Verifikasi Data Balita pada Dinas Kesehatan Kota Batu - Januar Muiz Triananda; Wildan Suharso (Institut Teknologi Garut, 2026)
Manual management of toddler data at the local health department level is prone to data duplication and inconsistencies; however, information system solutions that integrate technical aspects and organizational capacity are still rarely studied. This study aims to design and evaluate a web-based infant data verification information system for the Batu City Health Department. The system was developed using the Waterfall SDLC method with the Laravel 10 framework and MySQL, and was evaluated through Black Box testing and the System Usability Scale (SUS) with 10 respondents. Test results showed zero data duplication, verification time reduced from approximately 2 days to approximately 4 hours (an efficiency gain of approximately 70%), and a SUS score of 82.5, which falls into the “Excellent” category. These findings indicate that a user-centered design approach effectively enhances system acceptance among non-technical users, and that the combination of the Waterfall SDLC with the SUS constitutes an applicable development framework for health information systems in local government.